(untitled) (International Seven Journal of Health Research, 2024)
Rheumatoid cachexia can be described as a complex syndrome in which the patient loses muscle mass and may or may not maintain weight by gaining fat mass. The inflammatory cytokines active in rheumatoid arthritis seem to be the pivot of this process; high levels of TNF-alpha and IL-1 are associated with protein degradation. In this case report, information on the period of hospitalization was collected through a search of medical records, where the patient was admitted to hospital just over a month after surgery to repair an aortic aneurysm, reporting inappetence and weight loss, which had already been occurring for three months, even before the surgery. During hospitalization, hypotheses were raised about the cause of the weight loss, especially neoplasms. Finally, any diagnoses from other specialties were ruled out. The importance of recognizing cachexia as a warning symptom for patients with rheumatoid arthritis without clear manifestations of the disease was highlighted.